Augustine of Hippo: philosopher, exegete, and theologian ; a second collection of essays - Teske, Roland J. (Marquette studies in philosophy, 2009)
Ultimate reality according to Augustine of Hippo -- Augustine, Flew, and the free will defense -- Platonic reminiscence and memory of the present in St. Augustine -- Augustine of Hippo on seeing with the eyes of the mind -- St. Augustine's Epistula X : another look at "deificari in otio" -- St. Augustine, the Manichees, and the Bible -- The criteria for figurative interpretation in St. Augustine -- St. Augustine and the vision of God -- St. Augustine on the good Samaritan -- St. Augustine's use of "manens in se" -- St. Augustine on the humanity of Christ and temptation -- Augustine, Maximinus, and imagination -- The definition of sacrifice in the De ciuitate dei -- The image and likeness of God in St. Augustine's De Genesi ad litteram liber imperfectus